Traumatic hemothorax - Delbene, Roberto; Moure, Luis; Vázquez, Aníbal; Genta, Sandra; Viera, M F (Cirugía del Uruguay, 2002)
This study covers a population of 30 patients suffering from haemothorax, with reference to both medium and grave cases. The most frequent etiology was traumatic and the surgical technique employed most frequently was thoracic drainage; however in 9 cases the drainage was unsuccessful, which lead to a deferred thoracotomy for the purpose of performing an early decortication or pleural lavage.